Meningkatkan jati diri bangsa di zaman globalisasi dan digitalisasi: Peran pendidikan dan media sosial bagi generasi z - Aazaky, M Taufiqurrahaman (Maliki Interdisciplinary Journal, 2025)
The era of globalization and digitalization has had a major impact on the national identity of the Indonesian nation, especially among Generation Z who live in the rapid flow of global information. The main challenge faced is the penetration of foreign cultural values ​​that can erode the sense of nationality, the spirit of mutual cooperation, and the appreciation of the values ​​of Pancasila. This article aims to examine the strategic role of civic education and social media in strengthening national identity amidst rapid socio-cultural changes. The research method used is a literature study from various relevant scientific sources, with a descriptive-analytical approach.The results of the study show that civic education (PKn) has a crucial role in shaping the character of the younger generation based on Pancasila values, as well as fostering a sense of pride in national identity. In addition, social media as a digital interaction space has a dual influence: on the one hand it opens up opportunities to strengthen the national narrative through positive content, but on the other hand it also becomes a channel for the spread of foreign ideologies and information that can erode national values. Therefore, digital literacy and wise use of social media are important strategies in efforts to strengthen national identity. Strengthening Pancasila awareness is also a main pillar in building social cohesion and preventing division in the global era. Synergy between formal education, family, and community is needed to instill national values ​​in a sustainable manner. This article recommends the preparation of an adaptive PKn curriculum, strengthening character education based on national values, and creating social media content that promotes local culture and national history as a concrete effort to maintain the integrity of the nation’s identity in the digital era.